Räumliche Konzepte und sprachliche Strukturen - Habel, Christopher; Stutterheim, Christiane von (Linguistische Arbeiten, 2012)
For an interdisciplinary approach to linguistics spatial concepts are of especial significance in that they represent a link between linguistic and extra-linguistic cognition. In language production spatial representations form the starting-point for a class of linearization processes; vice versa, in language reception we have delinearization processes building up mental spatial representations from linguistic structures. Such processes are subject to restrictions specific to individual languages and resting on the respective relations between the language system and the conceptual system of spatial categories and relations.